First report of Haemaphysalis bispinosa, molecular-geographic relationships of Ixodes granulatus and a new Dermacentor species from Vietnam - Sándor Hornok; Jenő Kontschán; Gergő Keve; Nóra Takács; Dat Van Nguyen; Khanh Ngoc Phuong Ho; Tamás Görföl; Yuanzhi Wang; Róbert Farkas; Thanh Thi Ha Dao (Parasites & Vectors)
Abstract Background Vietnam and its region are regarded as an ixodid tick biodiversity hotspot for at least two genera: Haemaphysalis and Dermacentor. To contribute to our knowledge on the tick fauna of this country, ticks from these two genera as well as an Ixodes species were analyzed morphologically and their molecular-phylogenetic relationships were examined in taxonomic and geographical contexts. Methods For this study, seven Haemaphysalis sp. ticks were removed from dogs and collected from the vegetation. These showed morphological differences from congeneric species known to occur in Vietnam. In addition, three Ixodes sp. ticks were collected from pygmy slow lorises (Xanthonycticebus pygmaeus), and a Dermacentor female had been previously collected from the vegetation. After DNA extraction, these were molecularly or phylogenetically analyzed based on the cytochrome c oxidase subunit I (cox1) and 16S rRNA genes. Results The three species were morphologically identified as (i) Ixodes granulatus, which had nearly or exactly 100% sequence identities to conspecific ticks reported from large (approximately 2000 km) geographical distances but was more different (having lower, only 94.2% cox1 and 96.7% 16S rRNA sequence identity) from samples collected within 1000 km of Vietnam in Southern China and Malaysia, respectively; (ii) Haemaphysalis bispinosa, which showed 100% sequence identity to samples reported within both narrow and broad geographical ranges; and (iii) a new species, Dermacentor pseudotamokensis Hornok sp. nov., described here morphologically and shown to be phylogenetically a sister species to Dermacentor tamokensis. Conclusions Haemaphysalis bispinosa shows genetic homogeneity in the whole of South and Southeast Asia, probably owing to its frequent association with domestic ruminants and dogs (i.e. frequently transported hosts). However, I. granulatus, the Asian rodent tick, has a mixed geographical pattern of haplotypes, probably because it may associate with either synanthropic or wild-living rodents as primary hosts. This tick species is recorded here, for the first time to our knowledge, as parasitizing lorises in Vietnam and its region. Based on phylogenetic analyses, D. pseudotamokensis Hornok sp. nov., recognized and described here for the first time, was almost certainly misidentified previously as Dermacentor steini, drawing attention to the need to barcode all Dermacentor spp. in Southern Asia. Graphical Abstract